Perangkat Lunak Berbasis Web Menggunakan Metode Sistem Pendukung Keputusan Sebagai Seleksi Penerimaan Calon Karyawan Baru (Studi Kasus PT. Niki Harda Sentosa) - R. Wahyudi Darmawan (DPPM Universitas Pelita Bangsa, 2022)
Niki Harda Sentosa (PT.NHS) is a company engaged in sub-contactor sector in cooperation with large companies located in the Tangerang Regency area, cooperation in the form of sending young workers who are ready to go into employement. During this time, in the process of recruitment and selection of prospective employee, PT. NHS involves subjective elements and take a long time to select the appropriate employee candidates whoe are suitable with the criteria and also to speed up the selection process of candidates. The developmentof this system is using Analytical Hierarchy Process (AHP), Simple Additive Weighting (SAW) and Technique For Others Reference by Similarity to Ideal Solution (TOPSIS) for the decision method. The effectiveness of the decision support system software selection of new prospective employees by looking at the probability value of P-value is 2.3144E-07 smaller than 0.05 means that Ho is rejected or the application of the prospective employee appraisal system based on AHP, SAW and TOPSIS concepts runs precisely and accurately. Keywords : Decision Support System, AHP and TOPSIS, Employee